Normative Values and Psychometric Properties of Eq-5d-Y-3l in Chilean Youth Population Among Different Weight Statuses - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Background: This study aimed to provide population norms among children and adolescents in Chile using the EQ-5D-Y-3L questionnaire and to examine its feasibility and validity among body weight statuses. Methods: This was a cross-sectional study in which 2204 children and adolescents (aged 8–18 years) from Chile completed a set of questionnaires providing sociodemographic, anthropometric and health-related quality of life (HRQoL) data using the five EQ-5D-Y-3L dimensions and its visual analogue scale (EQ-VAS). Descriptive statistics of the five dimensions and the EQ-VAS were categorized into body weight status groups for the EQ-5D-Y-3L population norms. The ceiling effect, feasibility and discriminant/convergent validity of the EQ-5D-Y-3L were tested. Results: The dimensions of the EQ-5D-Y-3L questionnaire presented more ceiling effects than the EQ-VAS. The validity showed that the EQ-VAS could discriminate among body weight statuses. However, the EQ-5D-Y-3L index (EQ-Index) demonstrated a non-acceptable discriminant validity. Furthermore, both the EQ-Index and the EQ-VAS presented an acceptable concurrent validity among weight statuses. Conclusions: The normative values of the EQ-5D-Y-3L indicated its potential use as a reference for future studies. However, the validity of the EQ-5D-Y-3L for comparing the HRQoL among weight statuses could be insufficient. © 2023 by the authors.